Parameterized Littlewood-Paley Operators on Weighted Herz Spaces (Analysis in Theory and Applications, 2017)
The strong type and weak type estimates of parameterized Littlewood-Paleyoperators on the weighted Herz spaces $\dot{K}^{α,p}_q (ω_1,ω_2)$ are considered. The boundednessof the commutators generated by BMO functions and parameterized Littlewood-Paleyoperators are also obtained.
Keywords: Parameterized Littlewood-Paley operator; Herz space; weak Herz space; BMO; commutator; Muckenhoupt weight.